2020
DOI: 10.1016/j.compstruct.2019.111545
|View full text |Cite
|
Sign up to set email alerts
|

Specimen representation on the prediction of artificial test lightning plasma, resulting specimen loading and subsequent composite material damage

Abstract: Preceding work has established that artificial test lightning plasma and composite test specimen damage can be modelled. However, no work has studied the impact of specimen representation in the modelling of the plasma and the resulting impact on specimen damage. Herein four distinct specimen designs have been modelled to understand the impact on plasma properties. The resulting specimen surface loads have then been passed to Finite Element (FE) damage models to predict thermal damage. A magnetohydrodynamic FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…A mesh of 33,478 elements, with two elements through the thickness of each ply, was developed. Results of a previous publication indicated that most of the moderate and severe damage, generated by thermal-electrical loading, was confined to a region 30 mm from the centre of the specimen [21]. This region enclosed 87% of the moderate damage volume (and all moderate damage below ply two) and 99% of the severe damage (and all severe damage below ply one) as shown in Fig.…”
Section: Lightning Strike Simulationsmentioning
confidence: 73%
See 3 more Smart Citations
“…A mesh of 33,478 elements, with two elements through the thickness of each ply, was developed. Results of a previous publication indicated that most of the moderate and severe damage, generated by thermal-electrical loading, was confined to a region 30 mm from the centre of the specimen [21]. This region enclosed 87% of the moderate damage volume (and all moderate damage below ply two) and 99% of the severe damage (and all severe damage below ply one) as shown in Fig.…”
Section: Lightning Strike Simulationsmentioning
confidence: 73%
“…However, to-date these have typically been confined to simulations of a single type of lightning strike physics (thermal-electric, pressure-displacement, thermal-displacement) and have not accounted for the strain and heating rate effects observed during a lightning strike event. Preceding works which have studied the various physics individually indicated that mechanical damage plays an important role during Waveform A and thermal damage plays an important role under Waveform B conditions [15,21]. In general, given the individual physics studied in preceding works, there is limited understanding of the combined role or ratio of damage for the range of physical loading types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors have also used FE modelling to predict the likely damaged composite specimen due to incident current, temperature or pressure loading [17], [18], [20], [22], [23], [25], [35]- [37]. However, recently measures have been taken to combine plasma modelling and specimen material damage predictions [21], [24], [35], due to the complexity and computational burden of the required models. Thus limited understanding exists on the influence of plasma modelling on the prediction of specimen damage, and vice versa.…”
Section: Introductionmentioning
confidence: 99%